WORK FAMILY CONFLICT DAN FAMILY WORK CONFLICT SEBAGAI ANTESEDEN DARI BURNOUT SERTA PENGARUHNYA TERHADAP JOB PERFORMANCE KARYAWAN KAP SE-SULAWESI DAN PAPUA - Mardiana, Ana; Lukman; Tjiang Y. Suryady, Ardi; Limbunan, Excel (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study examines relationship of work family conflict and family work conflict as an antecedent of burnout and the affects to performance of Public Accountant who work at accounting firms in Sulawesi and Papua. The population in this study is a Public Accounting Firm in Indonesia, which is listed on the Indonesian Public Accounting Firm Directory 2018. Sampel of this study was public accountant who works in Sulawesi and Papua region. Data collection in this study was conducted using a survey method using a questionnaire against 73 employees from 15 public accounting firms throughout Sulawesi and Papua. The results of this study indicate that work family conflict and family work conflict as antecedents of burnout are not significantly related to job performance of Public Accountant who work at accounting firms in Sulawesi and Papua. In addition, the results of this study also identified a significant relationship between work family conflict on the burnout conditions of public accountant who work at accounting firms in the Sulawesi and Papua regions.